Lahjoita puhetta: a large-scale corpus of spoken Finnish with some benchmarks. - Moisio, Anssi; Porjazovski, Dejan; Rouhe, Aku; Getman, Yaroslav; Virkkunen, Anja; AlGhezi, Ragheb; Lennes, Mietta; Grósz, Tamás; Lindén, Krister; Kurimo, Mikko (Language Resources & Evaluation, 2023)
The Donate Speech campaign has so far succeeded in gathering approximately 3600 h of ordinary, colloquial Finnish speech into the Lahjoita puhetta (Donate Speech) corpus. The corpus includes over twenty thousand speakers from all the regions of Finland and from all age brackets. The primary goals of the collection were to create a representative, large-scale resource to study spontaneous spoken Finnish and to accelerate the development of language technology and speech-based services. In this paper, we present the collection process and the collected corpus, and showcase its versatility through multiple use cases. The evaluated use cases include: automatic speech recognition of spontaneous speech, detection of age, gender, dialect and topic and metadata analysis. We provide benchmarks for the use cases, as well downloadable, trained baseline systems with open-source code for reproducibility. One further use case is to verify the metadata and transcripts given in this corpus itself, and to suggest artificial metadata and transcripts for the part of the corpus where it is missing.